Recent advances in environmentally compatible polymers - Kennedy, John F. (John Fitzgerald), 1917-1963 (Woodhead Publishing Limited, 2006)
Based on the proceedings of the eleventh international Cellucon conference held in Tsukuba, Japan, this book offers a comprehensive overview of important research undertaken into all aspects of environmentally compatible polymers. It deals with natural and synthetic polymer materials such as gels, fibres, pulp and paper, films, foams, blends and composites and shows how environmental compatibility such as biodegradability and recyclability can be developed by utilising natural polymers such as polysaccharides and polyphenols. Based on the proceedings of the eleventh international Cellucon conference held in Tsukuba, JapanOffers a comprehensive overview of important research undertaken into all aspects of environmentally compatible polymersDeals with natural and synthetic polymer materials such as gels, fibres, pulp and paper, films, foams, blends and composites.